Institutional change in the German wage bargaining system: The role of big companies - Anke Hassel; Britta Rehder (Max Planck Institute for the Study of Societies, 2001)
Despite the emergence of new production systems, Europeanization and economic internationalization, the national arrangements of wage bargaining systems have not been eroded. The paper highlights the factors that counteract the pressures for a straightforward decentralization with reference to Germany. Firstly, the maintenance of peaceful labour relations is a major advantage for big companies in centralized wage bargaining systems. Secondly, big companies have been able to achieve labour cost control and the differentiation of working conditions by drawing up pacts for employment and competitiveness at the company level. Thirdly, they have succeeded in introducing a higher degree of flexibility into the collective agreement framework. The main argument will be that institutional change has taken other forms than expected. Whereas the formal institutional setting has remained relatively stable, the functioning of the German wage bargaining system has changed. – – Trotz der Verbreitung neuer Produktionssysteme, der Europäisierung und der wirtschaftlichen Internationalisierung sind nationale Tarifverhandlungssysteme in den meisten Ländern stabil geblieben. Dieses Working Paper hebt am Beispiel Deutschlands die Faktoren hervor, die dem Dezentralisierungsdruck entgegen wirken. Für Großunternehmen ist auch unter veränderten Bedingungen die Vermeidung von Konflikten einer der Hauptvorteile zentraler Tarifverhandlungssysteme. In dem gegebenen institutionellen Rahmen haben Unternehmen Möglichkeiten gefunden, über Standortsicherungsvereinbarungen auf Unternehmensebene die Arbeitsorganisation zu flexibilisieren und Arbeitskosten zu senken. Zudem konnten sie Tarifverträge flexibler gestalten und Öffnungsmöglichkeiten einfügen. Als Ergebnis wird festgehalten, dass institutionelle Veränderungen andere Formen angenommen haben als erwartet. Während die formalen institutionellen Rahmenbedingungen verhältnismäßig stabil geblieben sind, hat sich die Funktionsweise des deutschen Tarifverhandlungssystems verändert.
Keywords: 300